Application of the Stim-Hots Model Combined with Brainstorming Methods and SAC Media on Critical Thinking Skills and Student Motivation on Metabolism Materials - Hafnati Rahmatan; Andi Ulfa Tenri Pada; Samingan Samingan; Abdullah Abdullah; Meutia Bijeh Mata (Postgraduate, University of Mataram, 2022)
Students' low critical thinking skills are a problem that must be solved. Critical thinking is also related to motivation, because student motivation is seen as a necessary prerequisite for critical thinking skills. This study aims to determine the differences in the improvement of critical thinking skills and the differences in students' learning motivation using the Stim-HOTs learning model combined with the brainstorming method and SAC media on metabolic material. This study uses a quasi-experimental method withNonrandomized Control Group design, Pre-test Post-test Design.The sampling technique used purposive sampling technique with a total sample of 230 students consisting of the control group and the experimental group. The instrument used to measure critical thinking skills used 40 multiple-choice reasoned questions, while motivation was measured using 30 ARCS motivation questionnaires. Data analysis used independent sample t-test at a significance level of 0.05. The results showed that there were differences in the improvement of critical thinking skills and there were differences in students' learning motivation on metabolic material in class XII after the application of the Stim-HOTs learning model combined with the brainstorming method and SAC media. The conclusion of this study is that the Stim-HOTs learning model combined with the brainstorming method and SAC media can be applied to improve critical thinking skills and students' motivation to learn on the subject of metabolism